Evaluasi Kualitas Portal E-lerning Universitas Mahakarya Asia Menggunakan Metode MCCALL - Salamudin, Salamudin; Hartati, Sri; Saputro, Haris; Meilantika, Dian (Jurnal Nasional Ilmu Komputer, 2024)
This research focuses on evaluating the quality of the e-learning system at Universitas Mahakarya Asia using the McCall Method. The study aims to provide insights into the performance of the online learning platform e-learning.unmaha.ac.id. Involving criteria such as correctness, reliability, efficiency, integrity, usability, and maintainability, the research yields an overall score of 79.6%. The evaluation results indicate high reliability and integrity but highlight areas for improvement in the correctness of information and ease of maintenance. Improvement recommendations are provided to enhance content accuracy and improve the user interface for a smoother experience. Special emphasis is given to improving maintainability for the sustainability of the platform. These findings lay the foundation for developing a more user-responsive e-learning system, reinforcing the role of Mahakarya Asia University in providing quality online education